Strategies for incorporating evidence-based practice into nurse residency programs: A scoping review - Sampson, Marlene; Knupp, Amy; Chignolli, Holly; Dhakal, Kerry; Bulkowski, Kristi; Perdue, Justin; Warren, Samantha; Zellefrow, Cindy (Worldviews on evidence-based nursing, 2024)
The American Nurses Credentialing Center's (ANCC's) Practice Transition Accreditation Program (PTAP) establishes standards for nurse residency programs to elevate and optimize the skills, knowledge, and attitudes of new nurses participating in nurse residency programs. Evidence-based practice (EBP) is foundational to providing safe nursing care. One of the National Academy of Medicine's (NAM's) 2020 goals stated that 90% of clinical decisions would be supported by the best available evidence to attain the best patient outcomes. Nurse residency programs can benefit from evidence-based strategies to develop EBP competencies in new nurses. The purpose of this scoping review was to synthesize the literature around strategies for incorporating EBP into nurse residency programs across the United States. This scoping review was informed by the JBI (formerly known as the Joanna Briggs Institute) methodology for scoping reviews. Searches were conducted by a health science librarian in PubMed and CINAHL with Full Text. Keywords and their synonyms, Medical Subject Headings (MeSH; PubMed), and Subject Headings (CINAHL with Full Text) were used. Covidence, a literature review management program, was used to organize the literature and manage the review. Title, abstract, and full-text reviews were completed within Covidence using three teams of two independent reviewers. Four hundred and thirty-eight citations were imported into Covidence. Ten articles were retained for the final review. Three strategies for incorporating EBP into nurse residency programs emerged from the literature: (1) exposure of nurse residents to existing organizational resources, (2) completion of online EBP modules, and (3) completion of an EBP project. The incorporation of EBP competencies in nurse residency programs aligns with NAM's and ANCC's goals, yet a paucity of evidence exists to guide curriculum development in nurse residency programs. This scoping review corroborates the need for further research to inform best practices for implementing EBP into nurse residency programs.